Arranjos produtivos locais e desenvolvimento sustentável regional: uma proposição metodológica de análise aplicada no APL de confecção do sudoeste do Paraná - Marini, Marcos Junior (2012)
The world society is experiencing transformations triggered mainly from mid-twentieth century, including the economic, social, environmental, cultural, spatial, political and institutional. The literature pointed to factors such as globalization, technological advances and the restructuring of production systems as the main responsible for these changes. In this context, there is an orientation of the development process from territorial issues, as occurs in the articulation of local agents for the formation of clusters. Thus, clusters are at the center of contemporary debate on regional planning and regional development policies. Given the above, the general objective of this thesis is to build a methodological proposition to analyze the contribution of clusters to the process of regional sustainable development. Thus, is initially presented a framework configuration for this scenario, including the main components of cluster and its relations with the territorial dimensions. In sequence, is built a methodology of analysis with its application in four steps: selection of cluster, measurement of collective efficiency (IEC), measurement of regional impact (IIT), and the integration of these results on a panel called APL-DSR. Considering the methodological aspects, the research is classified as explanatory, with the method of case study. The data collection procedure was based on primary and secondary sources, including literature, documentary and field research. The case study was conducted at Clothing Cluster in Southwest of Paraná, with field research involving local actors of this productive arrangement, from the application of structured interviews. The results of the data collection were analyzed and interpreted in a quantitative and qualitative approach, following three referrals: a qualitative analysis of the responses of field research, analysis based on methodological proposal APL-DSR, temporal analysis based on simulations. The main results emphasizes that the Clothing Cluster in Southwest of Paraná achieved a good rating in the measurement of collective efficiency, reaching two thirds of the scale IEC. However, although positive, the territorial impact in the region analyzed was low, reaching a third of the positive range of the scale normalized IIT. Finally, highlights the contribution of this thesis, from the construction of the proposed methodology of analysis to assess the relation of cluster in the context of sustainable regional development, which could help both in decision making for public policy, as well as in the process of self-evaluation of cluster.